Safety, pharmacokinetics, and preliminary efficacy of E6201 in patients with advanced solid tumours, including melanoma: results of a phase 1 study - Tibes, Raoul (Br J Cancer, 2018)
BACKGROUND: This phase 1 first-in-human study aimed to determine the maximum-tolerated dose (MTD), dose-limiting toxicities, and safety of E6201, and to establish recommended dosing in patients with advanced solid tumours, expanded to advanced melanoma. METHODS: Part A (dose escalation): sequential cohorts received E6201 intravenously (IV) over 30 min (once-weekly [qw; days (D)1 + 8 + 15 of a 28-day cycle]), starting at 20 mg/m(2), increasing to 720 mg/m(2) or the MTD. Part B (expansion): patients with BRAF-mutated or wild-type (WT) melanoma received E6201 320 mg/m(2) IV over 60 minutes qw (D1 + 8 + 15 of a 28-day cycle) or 160 mg/m(2) IV twice-weekly (D1 + 4 + 8 + 11 + 15 + 18 of a 28-day cycle; BRAF-mutated only). RESULTS: MTD in Part A (n = 25) was 320 mg/m(2) qw, confirmed in Part B (n = 30). Adverse events included QT prolongation (n = 4) and eye disorders (n = 3). E6201 exposure was dose-related, with PK characterised by extensive distribution and fast elimination. One patient achieved PR during Part A (BRAF-mutated papillary thyroid cancer; 480 mg/m(2) qw) and three during Part B (2 BRAF-mutated melanoma; 1 BRAF-WT melanoma; all receiving 320 mg/m(2) qw). CONCLUSIONS: An intermittent regimen of E6201 320 mg/m(2) IV qw for the first 3 weeks of a 28-day cycle was feasible and reasonably well-tolerated in patients with advanced solid tumours, including melanoma with brain metastases, with evidence of clinical efficacy.